Quality assurance procedures for mass spectrometry untargeted metabolomics. a review - Dudzik, Danuta; Barbas-Bernardos, Cecilia; García, Antonia; Barbas, Coral (Journal of pharmaceutical and biomedical analysis, 2018)
[Display omitted] •Understanding metabolomics challenges helps to control unwanted variance.•Unwanted variation, bias and any source of possible errors should be minimized.•Quality assurance plays the crucial role in quality of metabolomics studies.•Standardized methods and SOPs for metabolomics are required. Untargeted metabolomics, as a global approach, has already proven its great potential and capabilities for the investigation of health and disease, as well as the wide applicability for other research areas. Although great progress has been made on the feasibility of metabolomics experiments, there are still some challenges that should be faced and that includes all sources of fluctuations and bias affecting every step involved in multiplatform untargeted metabolomics studies. The identification and reduction of the main sources of unwanted variation regarding the pre-analytical, analytical and post-analytical phase of metabolomics experiments is essential to ensure high data quality. Nowadays, there is still a lack of information regarding harmonized guidelines for quality assurance as those available for targeted analysis. In this review, sources of variations to be considered and minimized along with methodologies and strategies for monitoring and improvement the quality of the results are discussed. The given information is based on evidences from different groups among our own experiences and recommendations for each stage of the metabolomics workflow. The comprehensive overview with tools presented here might serve other researchers interested in monitoring, controlling and improving the reliability of their findings by implementation of good experimental quality practices in the untargeted metabolomics study.